Sustainability prioritization framework of biorefinery: A novel multi-criteria decision-making model under uncertainty based on an improved interval goal programming method. (1st April 2020) - Lin, Ruojue; Man, Yi; Lee, Carman K.M.; Ji, Ping; Ren, Jingzheng
Abstract: As a sustainable substitute of traditional petroleum refining technology, the biorefinery, which has advantages of higher resource utilization efficiency, better sustainability and lower negative environmental impacts, have developed and applied. However, the variety of developed biorefinery system makes it difficult for decision-makers to determine the most sustainable biorefinery system. How to deal with the uncertainties in the decision-making process is another issue existing in biorefinery prioritization. In order to solve the decision-making problem under uncertainties in the selection process of biorefineries, a novel decision-making framework based on an improved interval goal programming was developed. In this study, a case study, which is to select the most sustainable biorefinery technology from grain ethanol (GE), cellulosic ethanol (CE), and Fischer-Tropsch diesel (FTD), was adopted to practice the proposed method. Three other methods were also employed to validate the results determined by the proposed method in this study. The results revealed that FTD was recognized as the most sustainable scenario by the proposed method and the proposed method was validated and recognized as the most robust method in uncertain decision-making problem. Highlights: A novel framework was proposed for biorefinery systems ranking under uncertainties. The interval TOPSIS, interval GRA and TLGP methods were adapted for comparisons. FTD was recognized as the most sustainable scenarios. The framework was validated and recognized as a more robust method.